Manajemen Mutu Akademik SD Negeri Sudirman Kecamatan Ambarawa Kabupaten Semarang - Pratiwi, Suci Angga Kurnia; Miyono, Noor; Prayito, Muhammad (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Primary schools provide a strong foundation for individuals to understand basic knowledge and skills in various subjects such as language, mathematics, and science. Therefore, the academic quality of schools needs to be given significant attention to ensure these basic competencies are achieved. Academic quality cannot be separated from management implementation. This research focuses on analyzing the academic quality management at SD Negeri Sudirman based on the stages of planning, organizing, implementing, and controlling. The research approach used is qualitative. This type of research is a case study. Data collection techniques include interviews, observations, and documentation. The research uses source triangulation, technique triangulation, and time triangulation. Data analysis involves three steps: data reduction, data display, and conclusion drawing. The research results show that the planning stage is well-executed. This can be assessed from a series of planning activities aimed at improving academic quality, from identification to policy formulation and budgeting. The organizing stage is also well-executed, with task distribution tailored to the teachers' abilities and experiences. Coordination is carried out through a teachers' council forum that meets regularly. The implementation of academic quality management is effective with guidance and motivation from the principal. The controlling stage is also well-executed, indicated by routine evaluation processes and clear assessment indicators. The results of these evaluations and controls are then used to make further plans. Thus, the academic quality management process at SD Negeri Sudirman operates cyclically (planning, organizing, implementing, controlling, and back to planning). This is in line with general recommendations for educational management flow. This study recommends that the principal should strengthen a forum to facilitate the participation and involvement of parents in academic quality management. School leaders should also consider other forms of rewards, such as economic incentives, as part of their efforts to motivate teachers. This aims to further motivate teacher performance. Keywords: Educational Management, Academic Quality, School Management